Retail Supply Chain Management - Ayers, James B. (Auerbach Publications, 2012)
Demonstrating the link between markets, products, and product strategies in the supply chain, Retail Supply Chain Management provides the knowledge and skills required to thrive in this environment. It demonstrates the connection between the processes involved in manufacturing, distribution, warehousing, and transportation, and how to use these connections to their best advantage